Kaji Eksperimental Efektifitas Penyerapan Limbah Cair Industri Batik Taman Sari Yogyakarta Menggunakan Arang Aktif Mesh 80 dari Limbah Gergaji Kayu Jati - Novi Caroko, Sudarja , (Jurnal Semesta Teknika, 2012)
Utilization of teak wood saw scratches can be optimized by processing it becomes active charcoal which possesses higher economic value. The purpose of this study is to obtain mesh 80 activated charcoal made from teak sawing industrial waste and to determine itâs effectiveness in adsorbing heavy metals pollutant Cd, Pb, Cr, and colouring agent in liquid waste of batik industries. The charcoal is produced at ~5000 oC retort either for 4 hours or until white colour smoke does not appear. Charcoal was activated using H2SO4 at temperature of 5000 oC for 30 minutes in a furnace. There were 2 variables in this study, i.e weight of the activated charcoal (10, 15, 20 grams) and duration of the stirring (5, 10,15 minutes). Result of the research shows that activated charcoal made from teak wood saw scratches can be used as adsorbent in the liquid waste of batik industries such as heavy metals Cd, Pb, Cr, and dark colour. The colour gradation was found to decrease from 12600 TCU to 198 TCU, Pb content decrease from 0,189 mg/l to less than 0,0093 mg/L, Cd content decrease from 0,213 mg/l to less thanÂ  0,0093 mg/L, while Cr content decrease from 2,03 mg/l to 0,4205 mg/l.